THE ROLE OF THE YOUNGER GENERATION IN DEVELOPMENT CREATIVE ECONOMY IN BEKASI CITY - Indah Pangesti; Arief Nugroho Wibowo; Edward Alfin (Finance : International Journal of Management Finance, 2023)
The development of the creative economy has become the main focus for various cities seeking to achieve sustainable economic growth. The city of Bekasi, as one of the growth centers in Indonesia, is experiencing significant dynamics in the creative economy sector. This research aims to investigate the important role of the younger generation in encouraging the development of the creative economy in Bekasi City. The research results show that the young generation of Bekasi City has made a very significant contribution in a number of creative economic sectors, especially in the formation and development of start-up businesses. They create innovation and creativity that colors products and services, creating a unique identity that differentiates Bekasi City as a center for the creative economy. However, several significant challenges were identified, such as limited access to capital and funding, as well as shortages of certain knowledge and skills. This highlights the need for government and private sector support to create an environment that supports the growth of creative businesses and meets the needs of the younger generation. A number of strategic opportunities were also identified, including opportunities for cross-sector collaboration and the development of creative business networks. Government and private support can be optimized through policy incentives and regulatory facilitation that supports the growth of the creative economy sector. In conclusion, the younger generation plays an integral role in the development of the creative economy in Bekasi City. An action plan that focuses on solving challenges and exploiting opportunities can help create an environment that supports sustainable growth, have a positive impact on the local economy, and make Bekasi City a highly competitive center of innovation and creativity.